H3 histone methylation landscape in male urogenital cancers: from molecular mechanisms to epigenetic biomarkers and therapeutic targets - Burlibasa, Liliana; Nicu, Alina-Teodora; Chifiriuc, Mariana Carmen; Medar, Cosmin; Petrescu, Amelia; Jinga, Viorel; Stoica, Ileana (Frontiers in Cell and Developmental Biology, 2023)
During the last decades, male urogenital cancers (including prostate, renal, bladder and testicular cancers) have become one of the most frequently encountered malignancies affecting all ages. While their great variety has promoted the development of various diagnosis, treatment and monitoring strategies, some aspects such as the common involvement of epigenetic mechanisms are still not elucidated. Epigenetic processes have come into the spotlight in the past years as important players in the initiation and progression of tumors, leading to a plethora of studies highlighting their potential as biomarkers for diagnosis, staging, prognosis, and even as therapeutic targets. Thus, fostering research on the various epigenetic mechanisms and their roles in cancer remains a priority for the scientific community. This review focuses on one of the main epigenetic mechanisms, namely, the methylation of the histone H3 at various sites and its involvement in male urogenital cancers. This histone modification presents a great interest due to its modulatory effect on gene expression, leading either to activation (e.g., H3K4me3, H3K36me3) or repression (e.g., H3K27me3, H3K9me3). In the last few years, growing evidence has demonstrated the aberrant expression of enzymes that methylate/demethylate histone H3 in cancer and inflammatory diseases, that might contribute to the initiation and progression of such disorders. We highlight how these particular epigenetic modifications are emerging as potential diagnostic and prognostic biomarkers or targets for the treatment of urogenital cancers.